Analisis Relasi Kuasa Dalam Pengembangan Tata Kelola Pariwisata Berbasis Komunitas : Sebuah Pemetaan Bibliometrik - Yanti, Mutiara; Fajri, Hidayatul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The aim of this study is to assess the depth of research on power relations in the development of community-based tourist governance using a bibliometric approach. The database is searched using the Publish or Perish program, and the search results are extracted using VOSviewer. The topics were connected, according to the data analysis of the 5 clusters. VOSviewer can provide bibliometric mapping using the three primary visualization types of network visualization, overlay visualization, and density visualization. The two words that are used most frequently are community-based tourism and sustainable tourism. Through VOSviewer, several published articles were analyzed regarding power relations in the development of community-based tourism governance and found that research on power relations had never been carried out in community-based tourism.